Identification of a novel oxidation product from yellow fluorophore in the complex of apoPholasin and dehydrocoelenterazine. Issue 19 (1st October 2020) - Inouye, Satoshi; Nakamura, Mitsuhiro; Taguchi, Jumpei; Hosoya, Takamitsu
Graphical abstract: Highlights: The apoPholasin/dCTZ complex shows considerably weak continuous luminescence. The complex converts to blue fluorescent protein spontaneously. The oxidation products are coelenteramine (CTM) and a novel pyrazine compound (CTO). Chemical synthesized CTO was used for identification by mass spectrometry. CTM and CTO likely originate form imine intermediates of excited CTMD. Abstract: The complex of the recombinant fusion protein of apoPholasin and glutathione S -transferase (GST-apoPholasin) with non-fluorescent dehydrocoelenterazine (dCTZ) (GST-apoPholasin/dCTZ complex) shows yellow fluorescence at 539 nm by excitation at 430 nm. The GST-apoPholasin/dCTZ complex with a fluorophore (dCTZ*) has considerably weak luminescence activity, converting slowly to a blue fluorescence protein with the emission peak at 430 nm. The main oxidation products from dCTZ* for blue fluorescence were identified as coelenteramine (CTM) and an unreported pyrazine derivative, 3-benzyl-5-(4-hydroxyphenyl)pyrazin-2(1 H )-one (CTO) that was confirmed by chemical synthesis.